Expression of FLRT2 in Postnatal Central Nervous System Development and After Spinal Cord Injury - Li, Juntan; Shinoda, Yo; Ogawa, Shuhei; Ikegaya, Shunsuke; Li, Shuo; Matsuyama, Yukihiro; Sato, Kohji; Yamagishi, Satoru (Frontiers in Molecular Neuroscience, 2021)
Fibronectin and leucine-rich transmembrane (FLRT) proteins are necessary for various developmental processes and in pathological conditions. FLRT2 acts as a homophilic cell adhesion molecule, a heterophilic repulsive ligand of Unc5/Netrin receptors, and a synaptogenic molecule; the last feature is mediated by binding to latrophilins. Although the function of FLRT2 in regulating cortical migration at the late gestation stage has been analyzed, little is known about the expression pattern of FLRT2 during postnatal central nervous system (CNS) development. In this study, we used Flrt2-LacZ knock-in (KI) mice to analyze FLRT2 expression during CNS development. At the early postnatal stage, FLRT2 expression was largely restricted to several regions of the striatum and deep layers of the cerebral cortex. In adulthood, FLRT2 expression was more prominent in the cerebral cortex, hippocampus, piriform cortex (PIR), nucleus of the lateral olfactory tract (NLOT), and ventral medial nucleus (VM) of the thalamus, but lower in the striatum. Notably, in the hippocampus, FLRT2 expression was confined to the CA1 region and partly localized on pre- and postsynapses whereas only few expression was observed in CA3 and dentate gyrus (DG). Finally, we observed temporally limited FLRT2 upregulation in reactive astrocytes around lesion sites 7 days after thoracic spinal cord injury. These dynamic changes in FLRT2 expression may enable multiple FLRT2 functions, including cell adhesion, repulsion, and synapse formation in different regions during CNS development and after spinal cord injury.